ANALISIS STRUKTUR DAN MAKNA DALAM DRAMA SERIKAT KACAMATA HITAM KARYA SAINI KM - Deni Afriadi; Jefrizal Jefrizal (Universitas Lancang Kuning, 2022)
This research will analyze the structure of the play in the drama script of the Serikat Kacamata Hitam by Saini KM. The text of the manuscript will be analyzed using a non-interactive qualitative method (non interactive inquiry). Non-interactive research, also called analytical research, conducts studies based on document analysis. This study collects, identifies, analyzes and synthesizes data to then provide interpretations of concepts, policies, events that can be directly or indirectly observed. The source of data from non-interactive is documents. The play structure analysis used will describe the plot or story outline, characterization or characterization, dialogue or conversation, setting or foundation, theme or basic tone of the story, and the author's message or message in the text of Saini KM's Serikat Kacamata Hitam manuscript.